The relationship between Emotional Intelligence and Occupational Performance among librarians in public libraries, Malaysia / Mad Khir Johari Abdullah Sani - Abdullah Sani, Mad Khir Johari (Institute of Graduate Studies, UiTM, 2013)
This thesis reports the relationship between Emotional Intelligence (EI) and Occupational Performance (OP) of Malaysian Public Librarians (MPLibs). Public librarians are important assets since they are social agents that advocate a knowledge society development in Malaysia. As employees in service organizations, they are expected to be highly dynamic and provide quality services. These jobs involve understanding, communicating, empathizing with and learning from other members working in the organizations. These skills require not only a high degree of intellectual ability but a high level of EI. EI, therefore, seems to be considered essential for library employees understand other people’s feelings and for them to be involved in a relationship that will facilitate successful management and performance. This research employs a sequential exploratory mixed-method through semi structured interviews followed by a survey. Phase one of the preliminary study explored the librarians’ experiences and perceptions pertaining to EI through face-to-face interviews. Fourteen senior public librarians informed this phase of the study. The qualitative data were transcribed and coded based on Predetermined Concept Choice Mapping data analysis to refine and ascertain research model, variables, hypotheses and EI dimensions. 20 EI dimensions including 2 new dimensions were found and applied by MPLibs and help develop Public Librarian Emotional Intelligence Questionnaire (PubLIBEIQ)…